2012
DOI: 10.1002/eji.201142098
|View full text |Cite
|
Sign up to set email alerts
|

Human CD1c (BDCA‐1)+ myeloid dendritic cells secrete IL‐10 and display an immuno‐regulatory phenotype and function in response to Escherichia coli

Abstract: +subsets that display unique gene expression profiles, suggesting specialized functions. CD1c+ DCs express TLR4 while CD141 + DCs do not, thus predicting that these two subsets have differential capacities to respond to Escherichia coli. We isolated highly purified CD1c + and CD141 + DCs and compared them to in vitro generated monocyte-derived DCs (MoDCs) following stimulation with whole E. coli. As expected, MoDCs produced high levels of the proinflammatory cytokines TNF, IL-6, and IL-12, were potent inducers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 42 publications
8
81
1
Order By: Relevance
“…Expanded specific WT-1 126-134 ¡ T cells (Figs. 5 G-H) killed WT-1 126-134 , but not irrelevant KLK4 [11][12][13][14][15][16][17][18][19] peptide loaded T2 cells (Fig. 5I).…”
Section: Ivt-mrna Loaded Bdc Generate Primary Anti-viral and Antitumomentioning
confidence: 92%
See 1 more Smart Citation
“…Expanded specific WT-1 126-134 ¡ T cells (Figs. 5 G-H) killed WT-1 126-134 , but not irrelevant KLK4 [11][12][13][14][15][16][17][18][19] peptide loaded T2 cells (Fig. 5I).…”
Section: Ivt-mrna Loaded Bdc Generate Primary Anti-viral and Antitumomentioning
confidence: 92%
“…myeloid dendritic cells (mDC) can be subdivided into three populations: CD1c C , CD141 C (or XCR1 C ) and CD16 C mDC subsets. [12][13][14][15] Given the phenotypic and functional heterogeneity of BDC subsets, [16][17][18] it still remains unclear which might be best for therapeutic vaccination. The major myeloid CD1c C DC have been isolated clinically using a two-step immune selection technology, but these isolations take a long time and the low yields limit the DC vaccination dose.…”
Section: Introductionmentioning
confidence: 99%
“…CD1c + DCs and CD141 + DCs were isolated from PBMC by immuno-magnetic enrichment followed by flow sorting as previously described [13,30]. MoDCs were differentiated from CD14 + immuno-magnetically selected monocytes in the presence of GM-CSF and IL-4 as previously described [30].…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…Escherichia coli-activated CD1c 1 DCs suppressed allogeneic T-cell proliferation via IL-10. 94 These CD1c 1 DCs were characterized by low levels of production of TNF-a, IL-6 and IL-12, but high levels of production of the anti-inflammatory cytokine IL-10, and expression of the regulatory molecules IDO and soluble CD25. DCs conditioned by total coumarins of Urtica dentata Hand, a traditional herbal medicine, were maturation-resistant and expressed much lower MHCII (IAk) and CD86.…”
Section: Tol-dcs and Regulatory B Cells (Bregs)mentioning
confidence: 99%
“…Initial studies of DCs in human blood revealed that CD141 1 CD1c 1 DCs are equivalent to the mouse lymphoid resident CD8 1 DCs. 94 However, evidence for the immunosuppressive function of tol-DCs in humans has been limited to the use monocyte-derived DCs. Nevertheless, some achievements have been made in identifying the factors that modulate organspecific human DCs, as well as the underlying mechanisms for the negative regulation of the T-cell response by these tolerogenic cells.…”
Section: Tol-dcs and Regulatory B Cells (Bregs)mentioning
confidence: 99%